Insulin modulates the paired-pulse plasticity at glutamatergic synapses of hippocampal neurons under hypoinsulinemia - Shypshyna, Mariia; Kolesnyk, Oksana; Fedulova, Svitlana; Veselovsky, Nickolai (Frontiers in Cellular Neuroscience, 2023)
Hypoinsulinemia is a pathological consequence of diabetes mellitus that can cause a number of complications of the central and peripheral nervous system. Dysfunction of signaling cascades of insulin receptors under insulin deficiency can contribute to the development of cognitive disorders associated with impaired synaptic plasticity properties. Earlier we have shown that hypoinsulinemia causes a shift of short-term plasticity in glutamatergic hippocampal synapses from facilitation to depression and apparently involves mechanisms of glutamate release probability reduction. Here we used the whole cell patch-clamp recording of evoked glutamatergic excitatory postsynaptic currents (eEPSCs) and the method of local extracellular electrical stimulation of a single presynaptic axon to investigate the effect of insulin (100 nM) on the paired-pulse plasticity at glutamatergic synapses of cultured hippocampal neurons under hypoinsulinemia. Our data indicate that under normoinsulinemia additional insulin enhances the paired-pulse facilitation (PPF) of eEPSCs in hippocampal neurons by stimulating the glutamate release in their synapses. Under hypoinsulinemia, insulin did not have a significant effect on the parameters of paired-pulse plasticity on neurons of PPF subgroup, which may indicate the development of insulin resistance, while the effect of insulin on PPD neurons indicates its ability to recover the form of plasticity to the control level in normoinsulinemia, including the increasing probability of glutamate release in their synapses.